Dispatching Architecture and Planning Method of Future Distribution Network - Yinan ZHAO; Bin SONG; Zhenyu QIAN; Shunxin LI (Zhongguo dianli)
With the development of Internet of Things（IoT）technology, the large-scale access of smart terminal equipment is the general trend. At the same time, a large number of distributed generation access also has an impact on the distribution network architecture. This paper first studies the distributed architecture of distribution network in the future and puts for-ward the idea of distribution network which can transform between centralized form and distributed form. The evaluation and division method of coupling units are given. Then, the method of flexibility modeling is studied and applied to distribution network planning. Finally, an example is given to test the assumption.